Bhutan Development Update, August 2020 - World Bank (World Bank, Washington, DC, 2020)
Bhutan’s economy has been severely affected by Coronavirus 2019 (COVID-19) and the subsequent border closure to contain a domestic outbreak of the pandemic. In this context, economic growth is estimated to have decelerated from 3.8 percent in FY2018-19 to 1.5 percent in FY2019-20. Exports and imports have decreased significantly, in line with weak foreign and domestic demand and disruptions to trade. The government outlined a comprehensive national response to COVID-19 to protect vulnerable households and minimize the impact on employment, growth, and financial stability. Health measures are aimed at containing the pandemic and strengthening healthcare system resilience. The recovery of manufacturing and other exporting industries is likely to be gradual, because of the slowdown in India, Bhutan’s main export market. Similarly, the construction sector is expected to recover slowly reflecting a limited pipeline of public sector infrastructure projects.